The role of prehabilitation in improving brain health and cognition after chemotherapy in patients with colorectal cancer: Study protocol of the Chemo Brain Prehab Project - Katie Lauren Hoad; Chan Ton; Deborah Williamson; Daren Anselm Subar; Helen Elizabeth Nuttall; Christopher James Gaffney (PLoS ONE, 2026)
Introduction Regional disparities in the incidence of colorectal cancer remain a concern within the United Kingdom, particularly in the North West of England, with 37% higher incidences than the national average. Given the growing burden of treatment-related side effects such as cognitive impairment, this study aims to investigate whether prehabilitation can improve brain health and cognitive function in patients with colorectal cancer receiving adjuvant and neoadjuvant chemotherapy. Methods This randomised control trial will recruit eighty-six patients with stage II and III colorectal cancer, who will receive adjuvant and neoadjuvant chemotherapy (fluorouracil, capecitabine, or oxaliplatin) and will be randomised between prehabilitation and standard care groups. The prehabilitation group will be provided an individualised, home-based exercise programme before and during chemotherapy, multivitamin supplementation, telephone check-ins, and activity devices. The standard care group will be provided with information about physical activity and nutrition at the start of the intervention. Habitual physical activity will be tracked in all patients. Assessments will be conducted at baseline, 72 hours before the first chemotherapy administration, and 72–96 hours after the final treatment. Outcome measures will include cardiopulmonary fitness, neurotrophic biomarkers, electroencephalographic activity, cognitive function tests, and a cognitive-related quality of life assessment. Discussion This study protocol is designed to test whether home-based prehabilitation can improve brain health and reduce chemotherapy-related cognitive impairments in patients with colorectal cancer. Insights from this work may support the development of more accessible and effective prehabilitation programmes to address treatment specific cognitive impairment. Trial registration ClinicalTrials.gov NCT07341217